First Record Fungi for Iraq - Hussein, Al-Nasrawi (Journal of Fungal Diversity, 2018)
44fungal species were isolated from plant parts submerged in Al-Huwaiza marsh within Iraqi borders, and 7 new first records fungi in Iraq were isolated too, which have been illustrated and described as follows:- Carbosphaerella leptosphaeriodes, Curvularia lunata var.aria, Graphium sp., Helicascus kanaloanus, Leptosphaeria obions, Stagnospora sp. and Ulocladium tuberculatum, Carbosphaerella leptosphaeriodes, Curvularia lunata var. aeria, Graphium sp., Helicascus kanaloanus, Leptosphaeria obions, Stagnospora sp., Ulocladium tuberculatum.
Keywords: Fungi; Submerged plants; Marsh; new record; Iraq.